Effect of Sorption, Repeated Sorption and Desorption on Solubility and Swelling of the Polyester Resins - Narkhede, B.N.; Rathod, S.D.; Munde, A.S.; Chavan, F.R. (Asian Journal of Chemistry, 2010)
Different series of Polyester resins were prepared by partially esterifying poly (vinyl alcohol) with different amounts of terephthalic, isophthalic salicylic and p-hydroxy benzoic acid chlorides. Solubility and swelling degree of these products in water have been evaluated. To study how the solubility and swelling of the products were affected by repeated sorption, sorption and desorption of the product of each series used for sorption once were carried out. The solubility (g/mL) and swelling degree (g/g) were calculated. When the resin is subjected to reported sorption and desorption, a part of resin dissolves in water every time and swelling degree of the undissolved resin varies over a very narrow range.